The Effect of Feeding Laying Hens with Nonindustrial Hemp Seed on the Fatty Acid Profile, Cholesterol Level, and Tocopherol Composition of Egg Yolk - Yassine Taaifi; Kamal Belhaj; Farid Mansouri; Youssef Rbah; Reda Melhaoui; Nadia Houmy; Abdesammad Ben moumen; Embarek Azeroual; Mohamed Addi; Ahmed Elamrani; Hana Serghini-Caid (International Journal of Food Science)
The purpose of this study was to evaluate how cannabis-derived nonindustrial hemp seed (HS) inclusion in laying hen diets, as well as treatment duration, affected the fatty acid (FA) profile, cholesterol level, and tocopherol composition of egg yolks. Ninety-six (n=96) Lohmann Brown classic laying hens were randomly assigned to one of the four groups: control (standard diet) and HS-containing diets (10% HS, 20% HS, and 30% HS). The study was conducted for a period of 4 months. The findings demonstrated that the FA profile and the tocopherol composition are strongly impacted by the addition of HS to the diet of laying hens (p<0.05), but the cholesterol content remained unaffected. The increase in the dose of cannabis incorporated into the hen’s diet (HS-30% group) led to a significant increase in the amounts of the polyunsaturated fatty acids n-3 and n-6 content of egg yolk. This enrichment was accompanied by a considerable decrease in the n-6/n-3 ratio (p<0.001) from 8.19 to 4.88, on day 84 of the experiment. The total tocopherol content significantly increased (p<0.05) from 281.44 (control) to 327.02 μg/g yolk (HS-30%) on day 84. Finally, in the context of warfare, these seeds might be used as a feed additive for laying hens to produce higher nutritive value eggs with affordable prices.